2021
DOI: 10.14710/dimj.v2i1.9549
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Vitamin B1, B6, and B12 Forte Therapy in Peripheral Neuropathy Patients

Abstract: Background: Peripheral neuropathy can be caused by diabetes mellitus, nutritional deficiencies, entrapment or Carpal Tunnel Syndrome (CTS), and idiopathic.Objective: To determine the therapeutic efficacy of Vitamin B1, B6, and B12 forte in relieving symptoms of peripheral neuropathy.Methods: This was pre- and post-experimental study involving patients with moderate peripheral neuropathy (Toronto Clinical Neuropathy Score [TCNS] ≥6 and Michigan Neuropathy Screening Instrument [MNSI] ≥7) taken from outpatient ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…• Studies have indicated that the administration of vitamin B1, B6, and B12 forte therapy influences clinical outcomes, including pain and mobility, in patients with peripheral neuropathy stemming from diverse causes such as diabetes mellitus, nutritional deficiencies, entrapment or carpal tunnel syndrome, or idiopathic origins. [46].…”
Section: Discussionmentioning
confidence: 99%
“…• Studies have indicated that the administration of vitamin B1, B6, and B12 forte therapy influences clinical outcomes, including pain and mobility, in patients with peripheral neuropathy stemming from diverse causes such as diabetes mellitus, nutritional deficiencies, entrapment or carpal tunnel syndrome, or idiopathic origins. [46].…”
Section: Discussionmentioning
confidence: 99%
“…Berdasarkan tabel III vitamin B1 dan Neurobion digunakan untuk mencegah neuripati perifer. Menurut Silviana et al (2021) terapi untuk meredakan gejala neuropatik adalah antikonvulsan, antidepresan, dan agen neurotropik, yang termasuk vitamin B1, B6, dan B12. Pemberian vitamin B1, B6, dan B12 telah terbukti efektif mengatasi gejala neuropatik.…”
Section: Obat Premedikasi Kemoterapiunclassified